2012
DOI: 10.1111/1471-0528.12052
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐pregnancy body mass index, weight change during pregnancy, and risk of intellectual disability in children

Abstract: Objective This study investigated pre-pregnancy body mass index (BMI) and weight change in pregnancy as potential risk factors for intellectual disability (ID) in children.Design Retrospective cohort study.Setting South Carolina, USA. Methods We analysed South Carolina Medicaid data, linked to data from both the South Carolina Department of Education (DOE) and the South Carolina Department of Disabilities and Special Needs (DDSN). Maternal pre-pregnancy BMI and weight change during pregnancy were obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 57 publications
1
53
0
Order By: Relevance
“…Associations have been reported between prepregnancy obesity and intellectual disability, 12,16 lower cognitive performance, 10,13,14,17,21 ADHD, 11,19,20,32 and autism 15 in children. One null study was also reported; however, it was limited by assessing all overweight and obese women as a single group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Associations have been reported between prepregnancy obesity and intellectual disability, 12,16 lower cognitive performance, 10,13,14,17,21 ADHD, 11,19,20,32 and autism 15 in children. One null study was also reported; however, it was limited by assessing all overweight and obese women as a single group.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Recent epidemiologic studies suggest associations between prepregnancy obesity and various neurodevelopmental outcomes. [10][11][12][13][14][15][16][17][18][19][20][21] However, these studies were limited by small sample sizes, insufficient information on confounders and mediators, and imprecise neurodevelopment measures. Additionally, 1 study reported no association.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Several studies showed that maternal pre-pregnancy obesity is associated with a lower cognitive function in children, but results are not consistent [49][50][51][52][53][54][55][56][57] . Total weight gain during pregnancy seems not be associated with childhood cognitive function [54,56,60] . However, a study among 5,191 mother-offspring pairs of term deliveries from the UK showed small positive associations of maternal weight gain in each trimester of pregnancy with IQ scores at 8 years of age, without remarkable differences in strength of the effect estimates for different periods of maternal weight gain [61] .…”
Section: Childhood Outcomesmentioning
confidence: 95%
“…Data from the National Health and Nutrition Examination Survey (2009)(2010) state that 33% of American adults are overweight (body mass index: 25.0-29.9), 35.7% have mild or severe obesity (body mass index: 30.0-34.9 and body mass index: 35.0-39.9 respectively), and another 6.3% have morbid obesity (body mass index 40). The same data revealed that the proportion of childbearing-age (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) women that fall into 1 of the 3 obesity classes is 31.9%. 1 Although some weight gain during pregnancy is recommended, a recent study showed that the proportion of women who gain above the recommended amount for their body mass index category is 40%-60%.…”
mentioning
confidence: 93%
“…Fetal macrosomia is the major cause of cesarean deliveries and birth injuries such as shoulder dystocia. 22 In a previous study, 23 we examined maternal prepregnancy body mass index and weight change during pregnancy as potential risk factors for offspring intellectual disability. We found a significant association between prepregnancy body mass index and intellectual disability in children.…”
mentioning
confidence: 99%